Learning Management by Online Classroom Collaboration with a Community Enterprise: Taking Lessons from Thailand - Thongsri, Nattaporn; Seksan , Jariya; Tripak , Orawan (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study proposes and evaluates a tri-dimensional model for online learning in response to disruptions caused by a global health crisis. It examines learners’ attitudes, student and community stakeholder satisfaction, and differences in academic performance between STEM and non-STEM students. A total of 288 undergraduate students enrolled in business and technology programs participated in the study. Utilizing a mixed-methods approach, the study explores three core dimensions: (1) learners’ attitudes toward online learning, assessed using the uses and gratifications theory (UGT), focusing on cognitive, affective, and social needs, and analyzed using structural equation modeling (SEM); (2) student satisfaction and community feedback on online marketing deliverables, measured using descriptive statistics; and (3) comparative academic performance across disciplines, evaluated using inferential statistical tests. The findings reveal that all UGT variables significantly influence learners’ attitudes. Students expressed high satisfaction with the model’s real-world relevance, and community stakeholders reported similar satisfaction with the student-generated outputs. Furthermore, STEM students achieved significantly higher academic performance than their non-STEM peers.